Tracking training load and its implementation in tactical populations: A narrative review - Maupin, D.; Schram, B.; Orr, R. (Strength and Conditioning Journal, 2019)
Tactical populations often participate in demanding physical training and perform strenuous workplace tasks, increasing injury risk. Mitigating injury risk is vital for maintaining trained personnel and should be a focus for tactical populations. One such method, tracking training load, has not been studied in-depth in tactical populations, despite documented effectiveness in elite sport. Most injuries to tactical personnel are overuse in nature and therefore may be prevented by optimizing training load. Although the methods used in elite sport may not be directly transferrable to tactical environments, they may be used to inform injury mitigation strategies in tactical populations.